Building technology transfer within research universities : an entrepreneurial approach - Allen, Thomas J. (Thomas John), 1931-; O'Shea, Rory (Cambridge : Cambridge University Press, 2014)
For the past number of years, academic entrepreneurship has become one of the most widely studied topics in the entrepreneurship literature. Yet, despite all the research that has been conducted to date, there has not been a systematic attempt to analyze critically the factors which lie behind successful business spin-offs from university research. In this book, a group of academic thought-leaders in the field of technology transfer examine a number of areas critical to the promotion of start-ups on campus. Through a series of case studies, they examine current policies, structures, program initiatives and practices of fourteen international universities to develop a theory of successful academic entrepreneurship, with the aim of helping other universities to enhance the quality of their university transfer programs. This book is a valuable resource for university research administrators, technology transfer office professionals, academic entrepreneurs, incubator management officials, R&D managers, venture capitalists, researchers, policymakers, and others involved in the commercialization of intellectual property.
Building technology transfer within UCD to create a start-up environment Colm O'Gorman and Frank Roche; 10. Stimulating academic entrepreneurship and technology transfer: a study of King's College London commercialization strategies Mike Wright and Igor Filatotchev; 11. KU Leuven: complementing inception dynamics with incubation practices Petra Andries, Bart Van Looy and Koenraad Debackere; 12. Toward a'Global Knowledge Enterprise': the entrepreneurial model of the national university of Singapore Poh-Kam Wong, Yuen-Ping Ho and Annette Singh; 13. The path to the entrepreneurial university in China: a case study of Northeastern University, China Chunyan Zhou; 14. Public research organizations as a base for high-tech entrepreneurship in Europe: the case of IMEC and INRIA Philippe Mustar, Mirjam Knockaert and Bart Clarysse; 15. Conclusion: strategies for enhancement of academic entrepreneurship Rory O'Shea and Thomas J. Allen; Index.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Academic-industrial collaboration -- Case studies; Technology transfer -- Case studies